Development as a social process : contributions of Gerard Duveen - Moscovici, Serge; Jovchelovitch, Sandra; Wagoner, Brady, 1980- (New York : Routledge, 2013)
"This volume discusses the interface between human development and socio-cultural processes by exploring the writings of Gerard Duveen, an internationally renowned figure, whose untimely death left a void in the fields of socio-developmental psychology, cultural psychology, and research into social representations. Duveen's original and comprehensive approach continues to offer fresh insight into core theoretical, methodological and empirical problems in contemporary psychology. In this collection the editors have carefully selected Duveen's most significant papers to demonstrate the innovative nature of his contribution to developmental, social and cultural psychology. Divided into three sections, the book includes: Duveen's engagement with Jean Piaget the role of social life in human development and the making of cognition social representations and social identities Introduced with chapters from Serge Moscovici, Sandra Jovchelovitch and Brady Wagoner, this book presents previously unpublished papers, as well as chapters available here in English for the first time. It will be essential reading for those studying high level developmental psychology, educational psychology, social psychology, and cultural psychology"--
pt. 1. Piaget : a view from afar -- pt. 2. Development as decentration -- pt. 3. Thinking through social representations.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Duveen, Gerard; Developmental psychology -- Social aspects; Social psychology; Social representations; Electronic books